Resposta :
d = V(3 - 4)^2 + (7 - 2)^2
d = V(-1)^2 + 5^2
d = V1 + 25
d = V26
d= 5,09
Resposta: Opção a).
d = V(-1)^2 + 5^2
d = V1 + 25
d = V26
d= 5,09
Resposta: Opção a).
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{d_{PQ} = \sqrt{(x_Q - x_P)^2 + (y_Q - y_P)^2}}[/tex]
[tex]\mathsf{d_{PQ} = \sqrt{(3 - 4)^2 + (7 - 2)^2}}[/tex]
[tex]\mathsf{d_{PQ} = \sqrt{(-1)^2 + (5)^2}}[/tex]
[tex]\mathsf{d_{PQ} = \sqrt{1 + 25}}[/tex]
[tex]\mathsf{d_{PQ} = \sqrt{26}}[/tex]
[tex]\boxed{\boxed{\mathsf{d_{PQ} \approx 5,09}}}\leftarrow\textsf{letra A}[/tex]